Ferumoxytol and CpG oligodeoxynucleotide 2395 synergistically enhance antitumor activity of macrophages against NSCLC with EGFRL858R/T790M mutation - Wang G (Dove Medical Press, 2019)
Guoqun Wang,1 Jiaojiao Zhao,2 Meiling Zhang,1 Qian Wang,1 Bo Chen,3 Yayi Hou,2,4 Kaihua Lu11Department of Oncology, The First Affiliated Hospital of Nanjing Medical University, Nanjing 210029, People’s Republic of China; 2The State Key Laboratory of Pharmaceutical Biotechnology, Division of Immunology, Medical School, Nanjing University, Nanjing 210093, People’s Republic of China; 3Institute of Materials Science and Devices, Suzhou University of Science and Technology, Suzhou 215009, People’s Republic of China; 4Jiangsu Key Laboratory of Molecular Medicine, Nanjing University, Nanjing 210093, People’s Republic of ChinaPurpose: Drug resistance is a major challenge for epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKIs) treatment of lung cancer. Ferumoxytol (FMT) drives macrophage (MΦ) transformation towards a M1-like phenotype and thereby inhibits tumor growth. CpG oligodeoxynucleotide 2395 (CpG), a toll-like receptor 9 (TLR9) agonist, is an effective therapeutic agent to induce anticancer immune responses. Herein, the effect of co-administered FMT and CpG on MΦ activation for treating non-small cell lung cancer (NSCLC) was explored.Methods: The mRNA expression levels of M1-like genes in RAW 264.7 MΦ cells stimulated by FMT, CpG and FMT and CpG (FMT/CpG) were evaluated by quantitative reverse transcription PCR (qRT-PCR). Then, the effects of FMT/CpG-pretreated MΦ supernatant on apoptosis and proliferation of H1975 cells were detected by flow cytometry, and the expression of EGFR and its downstream signaling pathway in H1975 cells were explored by western blotting. Finally, a H1975 cell xenograft mouse model was used to study the anti-tumor effect of the combination of FMT and CpG in vivo.Results: FMT and CpG synergistically enhanced M1-like gene expression in MΦ, including tumor necrosis factor-α, interleukin (IL)-12, IL-1α, IL-1β, IL-6 and inducible nitric oxide synthase (iNOS). FMT/CpG-pretreated MΦ supernatant inhibited proliferation and induced apoptosis of H1975 cells, accompanied by down-regulation of cell cycle-associated proteins and up-regulation of apoptosis-related proteins. Further studies indicated that the FMT/CpG-pretreated MΦ supernatant suppressed p-EGFR and its downstream AKT/mammalian target of rapamycin signaling pathway in H1975 cells. Furthermore, FMT/CpG suppressed tumor growth in mice accompanied by a decline in the EGFR-positive tumor cell fraction and increased M1 phenotype macrophage infiltration.Conclusion: FMT acted synergistically with CpG to activate MΦ for suppressed proliferation and promoted apoptosis of NSCLC cells via EGFR signaling. Thus, combining FMT and CpG is an effective strategy for the treatment of NSCLC with EGFRL858R/T790M, mutation.Keywords: ferumoxytol, CpG oligodeoxynucleotide, macrophages, non-small cell lung cancer, epidermal growth factor receptor